Molecular simulations of potential agents and targets of Alzheimer's disease - Carlisle, Tanya (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
The World Alzheimer Report statedin 2016 that approximately 46.8 million people were living with dementia and this figure is expected to triple by 2050. Alzheimer's Disease was discovered to be a precursor to dementia in 1976 and since then efforts to understand Alzheimer's have been prioritized. To date, there are very few effective forms of treatment for Alzheimer's, many are known to offer only mild calming of the symptoms and have side effects such as diarrhea, nausea, loss of appetite and sleep disturbances. This has been due to lack of understanding on how Alzheimer's is caused. With the two main hallmarks of the disease now being more understood it has opened the doorway into the discovery of new treatments for this disease. This study focuses on the hallmark involving the aggregation of the Î²-amyloid protein to form plaques surrounding the neurons of the brain. Copper, Zinc and Iron have also been found in high concentrations in and surrounding these plaques. This study focused on the screening of the South African Natural Compound database (SANCDB) to discover hits that have potential destabilizing action against the Beta-amyloid aggregate. If one of these compounds could prove to have destabilizing action on the aggregate it could open the doorway to new potential forms of treatment. Over 700 SANCDB compounds were docked, and the top hits were taken to molecular dynamics to further study the interactions of the compounds and the aggregate. However, the hits identified had strong binding to the aggregate causing it to become stable instead of the desired effect of destabilizing the structure. This information, however, does not rule out the possibility of these compounds preventing the formation of the aggregates. Further, interactions of copper with Î²-amyloid and copper were determined by solubilizing the aggregate and introducing copper ions in a dynamics simulation. Possible interactions between copper and the methionine residues were visualised.
Keywords: Alzheimer's disease -- Treatment; Alzheimer's disease -- Molecular aspects; Amyloid beta-protein precurs; Amyloid beta-protein